Penentukuran Jarak Elektronik Menggabungkan Kaedah Pengukuran Zig-Zag Dengan Pelarasan Kuasa Dua Terkecil - Yahya, Azlan (2017)
There is a need for new EDM standard calibration procedures to fulfil the current market model of EDMs that uses infrared waves and visible light waves. Consequently, the standard conventional EDM test sites are presently unsuitable because the nature of wave properties and the purposes of EDM test today are different. The overall research objectives is to present a new EDM testing technique and to show the effectiveness of zig-zag distance measurement with reflection from front surface mirror on infrared and visible light waves EDM; introducing small EDM test site in laboratory; assessing the relevant elements in designing the test site that affects EDM accuracy measurement; forming the least squares method of statistical analysis for precise assessment on the quality of operation and the tests results; and producing a computer assisted decision support system in managing the measurement process. The research approach adopted includes observations and interviews, questionnaires distribution, analysis of previous EDM test data obtained from JUPEM’s records, environmental impact tests such as temperature and pressure, and assessment on the results of the least square adjustment. The research outcomes has successfully combined the design of new test site with least square adjustment technique specially developed for EDM tests that can produce standard error value up to 10-7m.